Home industry development through digital marketing with canva application optimization - Hernando, Riski; Rafiqi, Rafiqi; Hendriyaldi, Hendriyaldi; Hastuti, Dwi; Sukmawati, Nur (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2022)
This study aims to determine the home industry development on marketing performance through digital marketing by optimizing the Canva application in Lubuk Nagodang Village, Kerinci Regency, Jambi. The population in this study is MSMEs in Lubuk Nagodang Village, Kerinci Jambi Regency. While the sample of this research is MSMEs who take part in home industry development training through digital marketing by optimizing the Canva application. The results of this study indicate that there is an increase in marketing performance and sales performance during the Covid-19 pandemic after marketing training through digital marketing by optimizing the Canva application. The usefulness of this research can theoretically be used as a reference for further researchers by developing models with the latest digital marketing applications. In addition, it can be practically implemented by MSMEs in running their business.